ESCHATOLOGY AND PROPHECY: AN INTERTEXTUAL STUDY OF FAFIRRU ILALLÄH WORK - Fanani, Ahwan; Malik, Muhammad Fahad (Balai Penelitian dan Pengembangan Agama Makassar, 2024)
The Fafirru Ilallah is a Javanese texts contains the elements of eschatology and prophecy. The text indicates an acculturation between Javanese-Islamic eschatological work that explains Islamic eschatology. The acculturation makes the eschatological explanation in Fafirru Ila Allah nuanced in Islam and nuances of local culture to deal with actual societal challenge.This article aims to describe the content and the message of the text as well as to carry out intertextual analysis of the text with others. The article answers three main problems, namely the content of Fafirru Ila Allah, the message of it and intertextual link between the text with other prophetic literature. This paper uses an inter-textual and an intrinsic approach simultaneously.This paper reveals that Fafirru Ila Allahwork elaborates great apocalypse (qiyama kubra) and great apocalypse (qiyama sughra) in the lights of Islamic sources as well as local Javanese prophecy as contained in Serat Jayabaya, the Prophecy of Seh Subakir and the prophecy of Ranggawarsita. The work hints the vision of social control by providing the depiction of social crisis and how moslems such deal with it. The article, however, does not further discuss on pragmatical aspects of the texts or how it is received by Javanese readers.